Multi-scale variations in invertebrate and fish megafauna in the mid-eastern Clarion Clipperton Zone. (August 2020) - Simon-Lledó, Erik; Pomee, Christina; Ahokava, Akesa; Drazen, Jeffrey C.; Leitner, Astrid B.; Flynn, Adrian; Parianos, John; Jones, Daniel O.B.
Highlights: Patchy megafaunal density found across the north eastern CCZ region. Substantial regional taxonomic turnover between north eastern CCZ megafauna communities. Local variations of comparable magnitude to those observed at regional scale. Abstract: The abyssal seafloor of the Clarion Clipperton Zone (CCZ) in the central Pacific has the largest known deposits of polymetallic nodules and associated benthic faunal communities with high biodiversity. The environmental factors that structure these communities, both at regional and local scales, are not well understood. In this study, seabed image surveys were used to assess distribution patterns in invertebrate and fish megafauna (>1 cm) at multiple scales in relation to key environmental factors: food supply to the seabed varying at the regional scale (hundreds of km), seabed geomorphological variations varying at the broad local scale (tens of km), and seabed nodule cover varying at the fine local scale (tens of meters). We found significant differences in megafaunal density and community composition between all study areas. Variations in faunal density did not appear to match with regional productivity gradients, although faunal density generally decreased with increasing water depth (from E to W). In contrast, geomorphology and particularly nodule cover appeared to exert strong control on local faunal abundance and community composition, but not in species richness. Local variations in faunal density and beta-diversity, particularly those driven by nodule presence (within study areas), were of comparable magnitude to those observed at a regional level (between study areas). However, regional comparisons of megabenthic assemblages showed clear shifts in dominance between taxonomic groups (perceivable even at Phylum levels) across the mid-eastern CCZ seabed, suggesting a higher regional heterogeneity than was previously thought.